The Impact of Distance Learning on Identifying Primary Students with Specific Learning Disorder (SLD) during COVID-19 in Two Schools in Ajman City in the UAE - ABUHATTAB, MONA (2022)
Abstract The purpose of this study is to highlight the impact of distance learning on identifying primary students with specific learning disorders (SLD) during the COVID-19 pandemic in two private schools in Ajman city in the UAE. The present paper is a small-scale study that employed the qualitative design method to gather responses to the research question, depending on semi-structured interviews. A thematic analysis was used to analyze data collected from 101 teachers, parents, special education teachers, and coordinators. In light of the results, the study revealed that schools faced obstacles, which hindered the effective identification during distance learning. Findings referred these barriers to lack of knowledge and awareness about students with SLD, lack of instructions, resources, and data, as well as lack of assessment reliability and validity and poor student evaluation. In addition, there was lack of communication and coordination among teachers, special education teachers, coordinators, and parents. Lastly, the absence of a team of experts and trained teachers in the field played an important role. The study wrapped up with a list of recommendations for effective identification in an online environment such as training teachers on inclusive education, establishing a well-articulated and efficient policy for identification methods in the schools, and raising awareness within the school community. Also, stakeholders and policymakers are urged to examine the problem from different perspectives to overcome all the barriers hindering effective identification. Finally, various factors posed limitations to the study, including restricted access to schools, restrictive rules of social interaction during the pandemic, and having to rely solely on semi-structured interviews. The significance of this study arises from the sacristy of research, at least locally, and the increasing numbers of cases of learning difficulties, as well as the lack of awareness among all stakeholders on dealing with such cases. Keywords: distance learning, identification, COVID-19, students with a specific learning disorder.